Penerapan Media E-Comic dalam Pendidikan Karakter Kejujuran pada Mata Pelajaran Pendidikan Kewarganegaraan di SDN 16 Kota Langsa - Ayu Nafira; Lhutfia Wahyu Safutri (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Character education that combines honesty education into an important component of basic learning. This study aims to explain how the use of e-comic media can improve students' honesty in Citizenship (PKn) subjects at public elementary schools 16 in Langsa City. Qualitative methods were used, with limited observation of the learning process. E-comic media was chosen because it can convey moral values ​​visually and attractively for students. The findings of the study indicate that comics can encourage students' interest in learning PKn while instilling honesty values ​​contextually. Students find it easier to understand the meaning of honesty in daily routines because the characters and stories in e-comics help them learn. In conclusion, e-comics can be used well as an educational tool to instill honesty in elementary school students.